Dynamics of free amino acids in beef during thermal processing and mathematical modeling of doneness correlation - Jiayu Sun; Lifen Wang; Zehua Huang; Nianguo Guo; Hongzhou An; Xiaobin Zhan; Mehdi Abddollahi; Zoltan Kovacs (Food Materials Research)
This research investigates the dynamic changes of free amino acids in beef cooked to different doneness levels and develops a qualitative framework to predict doneness based on chemical attributes. During the frying process, beef proteins and free amino acids exhibit recognizable patterns that correspond to the central temperature. Myosin, being less thermally stable, exhibited a decreasing tendency at the first degree of doneness, while actin showed a distinct change at the fourth degree of doneness. The logarithmic curves adeptly fit hydrophilic and aromatic amino acids. Recognizing the nonlinear relationship between free amino acids and central temperature, Fisher's discriminant analysis was applied, achieving an 89.7% classification rate for non-enzymatic hydrolysis beef beef and 62.1% for enzymatically hydrolyzed beef. Therefore, the discriminatory accuracy for enzymatically hydrolyzed beef was deemed insufficient. By incorporating mean and covariance matrix parameters of beef doneness into a mathematical discriminative model, the discrimination accuracy could be enhanced to 96.55%.